Inorganic phosphate and the rapid mobilization of metabolic energy in neurons - Paul C. Rosen; Shivang Sullere; Panhui Fu; Juan R. Martínez-François; Daniel J. Brooks; Erica Kim; Chenghua Gu; Gary Yellen (Proceedings of the National Academy of Sciences, 2026)
Neurons experience brief, intense periods of energy demand when they are excited, but how they rapidly coordinate energy expenditure with production is incompletely understood. Part of the difficulty has been measuring the levels of molecules involved in this metabolic response with spatiotemporal precision in single live cells. Here, we engineered a quantitative fluorescent biosensor to monitor cytosolic inorganic phosphate (P i ), a fundamental component of energy metabolism that has a classically proposed but largely neglected role in activating glycolysis. Using two-photon fluorescence lifetime imaging, we observed millimolar increases in P i within seconds of stimulating mouse neurons both ex vivo and in vivo. Drawing on results from metabolic modeling, biosensor imaging, and enzymology, we argue that P i is a sensitive reporter of energy usage that potently links metabolic energy supply with demand in neurons. Quantitative live-cell imaging of P i should be a valuable approach for studying bioenergetics more generally.